Case Studies of IT transformations - Jain, Deepak (Indian Journal of Computer Science, 2019)
This paper presents case studies on IT transformations carried out to reduce OPEX, increase availability, and scalability of a not for profit organization. The first case is that of a US based non profit company facing daily challenges with their communication infrastructure. The paper describes the challenges, assessments phase, migration phase, and the benefits the customer received.